SYSTEMIC AND REGIONAL EXTRACORPORAL MANAGEMENT OF BLOOD STREAM AND MICROCIRCULATION IN CHILDREN WITH PERTHES DISEASE - N.N. Kulikov; I.V. Kirgizov; V.A. Dudarev; V.P. Sinyuk; I.A. Shishkin (Union of pediatricians of Russia, 2009)
The results of efficiency investigation of extracorporeal method of treatment at 56 early school age children and teenagers with III stage of Perthes disease after the operation are presented in this issue. The Doppler research in control and investigated groups was studied for treatment efficiency estimation.Key words: extracorporeal treatment, Perthes disease, children.